(untitled) (Research, Society and Development, 2020)
Introduction: Suicide is considered a public health problem. The World Health Organization estimates the occurrence of more than 800,000 suicide deaths in 2012 and about 1,600,000 suicide deaths in 2020. Brazil ranks eighth among the countries of the Americas, with the highest absolute numbers of suicides. In this context, this study aimed to identify the occurrence of suicidal behavior, including its phases, in university students in a city in the Midwest of São Paulo. Materials and Methods: This is a cross-sectional study, of a quantitative nature, carried out with 353 university students. Data collection in 2018, using semi-structured questionnaires prepared by the authors. Data analysis using descriptive and inferential statistics techniques (Pearson’s Chi-square test and Fisher’s exact test). The research project was approved by the Research Ethics Committee. Results: The suicidal behavior identified, comprising its phases, was: ideas of death (34.8%), suicidal ideation (26.1%), suicide desire (17.3%), suicide intention (8.2 %), suicide plan (9.3%) and attempted suicide (3.1%). The experience of suicidal behavior by university students was identified in all phases that comprise it. Discussion: The susceptibility of university students to the development of suicidal behavior is related to moments experienced, taken by feelings and anguishes. Demands of a single or collective order. Conclusions: Regarding academic variables and the relationship with the phases of suicidal behavior, an association was observed in relation to the undergraduate course.